Hubungan Psychologychal Capital Dengan Kebahagian Pada Wanita Dewasa Awal yang Mengalami Konflik Peran Ganda - Mutiara Mirah Yunita (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2019)
Based on a survey of women who carry out multiple roles as mothers, wives, and employees are found to be the least happy. Job-family conflict can affect job satisfaction, satisfaction with marriage, life satisfaction and happiness. Psychological capital has been shown to increase subjective well-being which can increase happiness. This study uses quantitative research methods with correlation techniques. The measuring instrument used is Subjective Happiness which has been adapted into Indonesian by researchers to measure happiness, PsyCap Quetionaire to measure psychological capital. The results in this study indicate that psychological capital has a significant positive relationship with happiness (sig = 0.00 <0.05, r = 0.46 **). When viewed per dimension, the four dimensions of psychological capital all have a significant positive relationship with happiness and the dimension that has the greatest relationship strength starts from hope (r = 0.565 **), self-efficacy (r = 0.404 **), resiliency (r = 0.393 **) and optimism (r = 0.384 **). A positive significant relationship indicates that the higher the quality of psychological capital possessed by participants, the higher the level of happiness of participants.